Análise dos padrões térmicos após estresse ao frio com utilização da termografia para identificação de suspeita do fenômeno de Raynaud - Heimbecher, Catia Terezinha (2018)
The thermography is a non-invasive instrument that detects the body’s infrared radiation. It is a method that presents no risks to the patient or the applicator and has as one of its applications the study of the Raynaud’s Phenomenon (FR). This is a condition that shows an exaggerated response to cold temperatures. In the case of secondary RF, ulcerations can occur at the extremities of the fingers and, in some cases, even amputations. Thermography can favor the diagnosis and adoption of early treatments, provided that the analysis standards are established, such as the distinction between the poststress reheat time in the cold and the reheating temperature range between people without and with the phenomenon, image parameters compatible with primary and secondary FR; among other gaps still existing. Thus, the objective of this study was to analyze the thermal patterns after cold stress with the use of thermography to identify the suspicion of RF. A descriptive exploratory study was performed, with 284 volunteers (257 undiagnosed individuals, 14 with a primary RF diagnosis and 12 with secondary RF diagnosis). The data collection environment was maintained at a temperature of 23 ° C, using the thermal camera (Fluke Ti400) to follow the reheating pattern after a cold stress protocol (immersion of the hands to carpal level in a container with water at 10 ° C for 60 seconds). The images were recorded: before, immediately after immersion and every 5 minutes, until 20 minutes after immersion. Regions of interest (ROI) were delimited at the distal end of the upper limbs and metacarpals. For the data analysis the normalized histograms were defined for the definition of the probability density function of absolute temperature and DDD (Distal Dorsal Difference). The recovery time after cold stress was 15 minutes and the temperature was above 25 ° C in the population that did not present late rewarming. The thermal images of patients with primary RF presented symmetry in all the fingers of both hands. In patients with secondary RF, the images presented asymmetry in 75% of the cases. A score was obtained from three symptoms, but the separability of the groups of individuals not diagnosed with RF was more consistent from the cold stress recovery cut-off line. When analyzing the thermal values of ROI's finger to finger, the thumb is spared in the FR, the 4th finger (annular) was revealed as a finger of greater significance and the second finger (index finger) was the coldest finger. It is understood that thermography can be used as a complementary exam, and the absolute temperature parameter presents better separability in the data. The DDD presented inconsistent in the thermal analysis.